1.25 GHz – 3.3 GHz broadband solid state power amplifier for L and S bands applications - Mohamed Ribate; Rachid Mandry; Jamal Zbitou; Larbi El Abdellaoui; Ahmed Errkik; Mohamed Latrach (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The research of a single stage broadband solid-state power amplifier based on ATF13876 transistor, which operates in the frequency ranging from 1.25 GHz ~3.3 GHz is presented in this paper. To achieve the broadband performance of the operating bandwidth, a multi-section quarter wave impedance transformer and an approximate transformation of previously synthesized lumped elements into transmission lines are adopted. With neatly design of broadband matching networks and biasing circuit, excellent matching performances and unconditionally stability are achieved over the whole operating bandwidth with a maximum gain of 17.2 dB. The large signal simulation shows that the proposed circuit reaches a saturated output power of 18.12 dBm with a maximum PAE of 27.55% and a 1-dB compression point at 5 dBm input power level. Considering the wide frequency coverage, the features of the proposed design compares favorably with the contemporary state-of-the-art.